Comparative analysis of image quality parameters and spatial resolution of three Small Animal PET scanner in Brazil (Brazilian Journal of Radiation Sciences (BJRS), 2023)
This study evaluated Image Quality (IQ) parameters and spatial resolution (SR) of Triumph® LabPET systems installed in three different Brazilian preclinical molecular imaging centers. A comprehensive evaluation of the PET scanner intrinsic parameters is important to optimize the acquired images, providing more reliable qualitative and quantitative analyses. Experiments were carried out at the centers: C1 - Molecular Imaging Laboratory of the CDTN/CNEN; C2 - Laboratory of Nuclear Medicine of HCFMUSP; C3 - Preclinical Research Center of the Brain Institute at PUC-RS. IQ phantom PET images were acquired as recommended in NEMA NU 4-2008 standard. Image reconstructions were performed in each system using the same reconstruction protocol. Data was processed using PMOD® software. The IQ parameters: (i) uniformity, (ii) spill-over ratio (SOR) and (iii) recovery coefficients (RC) were evaluated and compared. For Uniformity test, the percentage standard deviations of mean activity concentration were 7.8%; 7.3% and 6.4% for Centers 1, 2 and 3 respectively. Cold chambers RSO values in the systems 1, 2 and 3 were respectively 0.16, 0.19 and 0.21 for water; 0.26; 0.28 and 0.30 for air. The RC’s for rod diameters from 1 to 5 mm ranged from 0.08 to 0.91 for the three centers. Results revealed that the three PET systems have appropriate quality parameters for pre-clinical studies, presenting values compatible with international standards. This study was able to reveals the performance of preclinical PET system of different Brazilian imaging centers and may support the standardization of a National Quality Control Program for Small Animal PET scanners.